Pendampingan Pengelolaan Sampah pada TPS 3R Desa Jenggala Kabupaten Lombok Utara Menuju Ekonomi Sirkular - Baiq Harly Widayanti; Aprilian Maulana; Rifki Nur Juliadi; Lalu Septiya Fahmi Rezi; Lina Mardiana; Joni Safaat Adiansyah (Universitas Mataram, 2026)
North Lombok Regency has 19 TPS 3R (Reduce, Reuse, Recycle) waste management units; however, the majority are not operating optimally. One of the active facilities is TPS 3R Jenggala Mandiri in Jenggala Village, Tanjung District, which faces a primary challenge related to the absence of household-level waste segregation at the source. This condition limits the availability of organic feedstock for compost production and increases the operational burden on facility managers due to additional sorting requirements. This community engagement program aimed to strengthen waste management practices through educational and technical assistance focused on source-based segregation of organic and inorganic waste. The implementation was structured into three phases: (1) a preparatory phase involving coordination with TPS 3R management; (2) an implementation phase comprising community outreach, practical demonstrations, and the provision of composting equipment (composter bags, buckets, EM4 bioactivator, and molasses); and (3) an evaluation phase conducted through post-activity monitoring and follow-up. The outreach activities were attended by 52 participants from Nurul Huda Hamlet, during which 25 buckets and 22 composter bags were distributed. The results indicate a positive behavioral shift, as several households initiated independent segregation of organic waste and began producing compost. Nevertheless, full community participation has not yet been achieved. Key constraints identified include limited technical understanding regarding the preparation and mixing of fermentation agents, as well as institutional instability due to changes in TPS 3R management. Overall, the findings suggest that structured education and intensive mentoring can enhance community awareness and promote household-level waste segregation practices. However, sustained institutional support and continuous technical assistance are required to ensure long-term effectiveness and optimal operational performance.